2013
DOI: 10.7243/2052-6180-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance patterns in extended-spectrum β-lactamase producing Escherichia coli and Klebsiella pneumoniae isolates in a private tertiary hospital, Kenya

Abstract: Background: Extended-Spectrum β-Lactamase (ESBL) producing Enterobacteriaceae have become widespread in hospitals and are increasing in community settings where they cause a variety of infections. In addition to hydrolyzing most beta-lactam agents, bacteria harboring these enzymes display resistance to other unrelated antimicrobial agents and thus often pose a therapeutic dilemma. Though these resistance patterns have been studied elsewhere within Africa, such data from hospitals in Kenya are scanty. We theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 16 publications
11
24
0
Order By: Relevance
“…Extended spectrum beta-lactamases (ESBLs) have been reported as one of the most important hospital-acquired infections such as burn infection and bacteremia 9,55 . Most bacteria harboring ESBLs are usually resistant to beta-lactam antibiotics and other classes of antimicrobials 56 . These enzymes are carried in and transferred from bacteria to bacteria by plasmids 57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Extended spectrum beta-lactamases (ESBLs) have been reported as one of the most important hospital-acquired infections such as burn infection and bacteremia 9,55 . Most bacteria harboring ESBLs are usually resistant to beta-lactam antibiotics and other classes of antimicrobials 56 . These enzymes are carried in and transferred from bacteria to bacteria by plasmids 57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Ankur et al on clinical isolates of ESBL producing E. coli , resistance found to amikacin was 14.7%, gentamicin 66.7%, trimethoprim/sulfamethoxazole 79.1%, and ciprofloxacin 93.8% 25. Maina et al documented a higher proportion of isolates resistant to ciprofloxacin, levofloxacin, and tetracycline, and approximately 100% sensitivity to carbapenems 26. Al-Zarouni et al also demonstrated high resistance rates to fluoroquinolones and cephalosporins and higher susceptibility rates to carbapenems and amikacin 27…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to the result of Sarkar et al 22 , who found similar resistance pattern (78.9% & 64% respectively). Besides, there are more studies 23,24 with similar results indicating high level resistance to ciprofloxacin. This increased resistance might be due to widespread indiscriminate use, their oral route of ORIGINAL ARTICLE administration, easy availability and affordability of ciprofloxacin over the country.…”
Section: Discussionmentioning
confidence: 92%